STRATEGI KOMUNIKASI DINAS TENAGA KERJA KOTA PEKANBARU DALAM MENGINFORMASIKAN PASAR KERJA KEPADA PENCARI KERJA - Devamia, Zalikha; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Role of the Department of Labor Pekanbaru is informing the labor market to the public in accordance with the qualifications needed by the company, so that the public can obtain the exchange of information and have the opportunity to meet the qualifications required of the company. Public in here are the people who need the information placement and expansion of employment opportunities at the Department of Labor as government agencies who have the duty and function in providing the information needed it. Procedures carried out in the Department of Labor job is to convey information to receive job information from companies that need workers, then paste the information in the form of job advertisements in Pekanbaru City Department of Labor in full accompanied by qualification requirements needed.This study is a qualitative research that is by exposing the whole data obtained from interviews descriptively, all information relating to the object of the study was obtained from the informant study of 10 people that all employees at the Job Agency Affairs at the Department of Labor Pekanbaru.The study states that the Strategy of Development Communicators Placement and Extension of Employment at the Department of Labor Pekanbaru in informing the labor market and the labor market to job seekers, among others: (a). A transmitter of information (Who), the strategy of the Department of Labor is as a medium conveys information to the public labor market. (b). Delivering Information (Say What), the Department of Labor through Section Labour Market Information and Job Fair to take an active role in providing information that is easily understood, understood by the public in connection with the labor market informed. (c). Communication Channels (In Which Channel), the Department of Labor is to disseminate information to the public media / public. (d). Delivering Information kepublik (To Who), the Department of Labor as a medium conveys information about the job market of the company hiring to the public. (e) the effect is (whith what effect), communication within an organization is required to get the information so that the activities or tasks that run run in accordance with the objectives to be achieved.Keywords: Strategy, Communications, Labour Market Information